2021
DOI: 10.1101/2021.10.22.465320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PRMT1 regulates EGFR and Wnt signaling pathways and is a promising target for combinatorial treatment of breast cancer

Abstract: Identifying new therapeutic strategies for triple-negative breast cancer (TNBC) patients is a priority as these patients are highly prone to relapse after chemotherapy. Here, we found that protein arginine methyltransferase 1 (PRMT1) is highly expressed in all breast cancer subtypes. Its depletion decreases cell survival by inducing DNA damage and apoptosis in various breast cancer cell lines. Transcriptomic analysis and chromatin immunoprecipitation revealed that PRMT1 regulates the epidermal growth factor re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(122 reference statements)
1
1
0
Order By: Relevance
“…An interesting finding reported that protein arginine methyltransferase 1 (PRMT1) is overexpressed in all BC subtypes, and its reduction hindered cell growth by induction of DNA damage response and apoptotic pathways in BC cells. The same finding proved that PRMT1 regulates EGFR and Wnt-mediated signalling in TNBC through transcriptomic and chromatin immunoprecipitation analysis (Suresh et al 2021). PRMT1 inhibitors showed anti-tumour activity in TNBC xenograft models.…”
Section: Egfr-activated Signalling Pathways: Potential Contributors I...supporting
confidence: 57%
See 1 more Smart Citation
“…An interesting finding reported that protein arginine methyltransferase 1 (PRMT1) is overexpressed in all BC subtypes, and its reduction hindered cell growth by induction of DNA damage response and apoptotic pathways in BC cells. The same finding proved that PRMT1 regulates EGFR and Wnt-mediated signalling in TNBC through transcriptomic and chromatin immunoprecipitation analysis (Suresh et al 2021). PRMT1 inhibitors showed anti-tumour activity in TNBC xenograft models.…”
Section: Egfr-activated Signalling Pathways: Potential Contributors I...supporting
confidence: 57%
“…PRMT1 inhibitors showed anti-tumour activity in TNBC xenograft models. Therefore, a combinational inhibition therapy targeting EGFR and PRMT1 would be a valuable therapeutic approach for TNBC patients (Suresh et al 2021). In regards, to the combinational therapy, neratinib (HER2 inhibitor) in combination with capecitabine (pyrimidine derivatives as an anti-metabolite agent to treat BC), was approved on February 25, 2020, by U.S. FDA for the treatment of metastatic or advanced HER2+ BC patients (Xuhong et al 2019).…”
Section: Egfr-activated Signalling Pathways: Potential Contributors I...mentioning
confidence: 99%